Síntese e caracterização de nanopartículas superparamagnéticas de CoFe2O4 e NiFe2O4 via método sol-gel protéico e com o uso de um forno de lâmpadas halógenas - Maia, André de Oliveira Girão (2022)
This work deals with the synthesis of superparamagnetic nanoparticles of cobalt ferrite and nickel ferrite, through the protein sol-gel method, which uses gelatin as an organic precursor, and a rapid thermal processing furnace that uses halogen lamps as a heat source. XRD, TEM, M × H, FC, ZFC and Mössbauer Spectroscopy measurements were performed to characterize the samples. Nanoparticles with an average size of 5-10 nm and microstrain of the order of 10-4-10-3 were obtained for cobalt ferrite and for nickel ferrite the average size was 6-12 nm and the microstrain of the order of 10-4-10-2. The increase in coercivity and remanence was observed with increasing nanoparticle size for both materials. Saturation magnetization decreased with particle size reduction due to the formation of a disordered layer on the surface. Mössbauer spectroscopy showed an increase in the amount of superparamagnetic nanoparticles for samples with smaller nanoparticles and with less dispersion.